Efficacy of disinfection of endoscopes contaminated by Streptococcus equi subspecies equi. - Nadruz, Veridiana Azevedo (Kansas State University, 2022)
Prevention of spread of Streptococcus equi subspecies equi (S. equi) following an outbreak is best accomplished by confirming negative bacterial status through endoscopic lavage of the guttural pouch, with samples tested by culture or/and real time polymerase chain reaction (qPCR). It is critical that high-level disinfection of endoscopes eliminates live bacteria and DNA to avoid the false diagnosis of carrier horses of S. equi. The objective of this study was to report the failure rate (by culture and qPCR) of high-level disinfection of endoscopes contaminated with S. equi with two different disinfectants, accelerated hydrogen peroxide (AHP) and ortho-pthaldehyde (OPA). The second objective of this study was to determine if AHP and OPA disinfectants were equivalent for disinfection of endoscopes. Two endoscopes were contaminated with a standard S. equi broth suspension. The endoscopes were disinfected with AHP, OPA or control (water). In a randomized block design, endoscopes were contaminated and disinfected 30 times for each disinfectant (15 disinfections performed per day for 6 days). Samples were collected before and after disinfection and submitted for detection of S. equi by culture and qPCR assay. Using multivariable logistic regression model adjusted probability with endoscope and day as controlled variables the probability of an endoscope being qPCR was determined. Following contamination all endoscopes were positive for S. equi culture and qPCR. After disinfection, all endoscopes were culture negative. However, qPCR testing was positive for S. equi for endoscopes treated with AHP, 10/30, with OPA, 22/30, and with water, 21/30 following disinfection. Use of the AHP disinfectant resulted in a significantly lower probability of being PCR-positive after disinfection (31%) compared to disinfection with OPA (81%) and control (72%). High-level disinfection of endoscopes contaminated with S. equi resulted in high failure rate in successfully removing DNA. The AHP disinfectant was more effective than the OPA product, however, it was less effective in removing DNA. Therefore, horses could be falsely diagnosed as carriers of S. equi, if the testing is based on qPCR assay only. Further studies are needed to better understand the carrier S. equi horses.
Keywords: Strangles; Disinfection of endoscopes; PCR; Culture